1970
DOI: 10.1128/mmbr.34.1.1-19.1970
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry and regulation of streptomycin and mannosidostreptomycinase (alpha-D-mannosidase) formation.

Abstract: A new field of research has been opened to us; the possibility of elucidating many complex natural processes heretofore not sufficiently understood and of discovering new agents that may help man in controlling diseases. .. is certainly inviting." Selman A. Waksman, 1943

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0
1

Year Published

1971
1971
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 60 publications
(112 reference statements)
2
15
0
1
Order By: Relevance
“…The syntheses of alkaline phosphatases are derepressed in low-Pi environments (11). Possible roles of alkaline phosphatases and of dephosphorylation have been suggested in the formation of such secondary metabolites as streptomycin, lincomycin, viomycin, vancomycin, and pyocyanine (2,8,14). With the latter two, alkaline phosphatase activity was observed to increase just before the onset of synthesis of the secondary material; in this study, we made the same observation with prodigiosin and also showed that the increased activity failed to occur in noninduced cells.…”
Section: Discussionmentioning
confidence: 99%
“…The syntheses of alkaline phosphatases are derepressed in low-Pi environments (11). Possible roles of alkaline phosphatases and of dephosphorylation have been suggested in the formation of such secondary metabolites as streptomycin, lincomycin, viomycin, vancomycin, and pyocyanine (2,8,14). With the latter two, alkaline phosphatase activity was observed to increase just before the onset of synthesis of the secondary material; in this study, we made the same observation with prodigiosin and also showed that the increased activity failed to occur in noninduced cells.…”
Section: Discussionmentioning
confidence: 99%
“…Samples of the culture were removed, centrifuged, and washed once with 0.85% NaCl. The mycelium was suspended in 3 to 4 volumes of cold deionized water and disrupted in a Branson sonifier (Heat Systems Co.) for 2 min in four 30-sec bursts. The disrupted suspensions were then centrifuged at 12,000 rev/min for 20 min in a refrigerated Sorvall RC-2 centrifuge to remove intact cells and cellular debris.…”
mentioning
confidence: 99%
“…A. parasiticus ATCC 15517 (formerly known as A. flavus) was used throughout the study and was maintained as a soil culture. Five-to- 7 day-old spores, obtained from a bottle containing 50 ml of glucose-peptone-agar, were distributed equally to five 500-ml Erlenmeyer flasks containing 100 ml of sterile basal medium. These flasks were incubated at 26 i 1 C on a rotary shaker or as stationary cultures for 8 days unless otherwise stated.…”
mentioning
confidence: 99%